Associação entre dispersão mecânica miocárdica, fibrose e arritmogenicidade ventricular na cardiomiopatia chagásica - Alda Cristina Alves de Azevedo (2023)
Chronic Chagas cardiomyopathy is considered the most fibrosing of the known myocarditis and also one of the most arrhythmogenic of the known heart diseases, which can give rise to complex arrhythmias. Myocardial mechanical dispersion may result from heterogeneous electrical conduction and is associated with ventricular arrhythmias. The present study investigated the association between mechanical dispersion and the presence of left ventricular fibrosis assessed by cardiac magnetic resonance using the delayed enhancement technique in patients with chronic chagasic cardiomyopathy. Methods: Forty-five patients with chronic Chagas cardiomyopathy were included. Left ventricular function was assessed by left ventricular ejection fraction (LVEF) and global longitudinal strain assessed by speckle tracking echocardiography. Mechanical dispersion (MD) was calculated as standard deviation of the time from Q/R on the ECG to peak longitudinal strain in 16 segments of the left ventricle. Late gadolinium enhancement was assessed by cardiac magnetic resonance (CMR) imaging. Dynamic electrocardiography was performed to evaluate the frequency and complexity of ventricular extrasystoles (VES). Results: LV MD was 80 ms [interquartile range (IQR) 50-75]. In linear regression, when corrected for LVEF, LVd, E/e' ratio, NYHA, ESV, bigeminy, pairs, and non-sustained ventricular tachycardia, MD was associated with several late enhancement assessment measures such as massLGE6D (p=0.045), massLGE3D (p=0.017), massManual (p=0.016), %manual (0.028). A correlation was observed between DM and the presence of bigeminism (r=0.331, p=0.027), ESV (r=0.329; p=0.027), pairs (r=0.310; p=0.038), non-sustained ventricular tachycardia (r=297; p =0.048), LVEF (r=-0.561; p<0.001) and GLS (r= -0.702; p<0.001). Conclusion: MD, assessed by the speckle tracking technique, proved to be useful in predicting myocardial fibrosis assessed by CMR, showing the probable relationship between ventricular arrhythmia and fibrosis in Chronic Chagas cardiomyopathy.